Dorsal root ganglion neurons recapitulate the traumatic axonal injury of CNS neurons in response to a rapid stretch in vitro - Adams, Alexandra A.; Li, Ying; Kim, Haesun A.; Pfister, Bryan J. (Frontiers in Cellular Neuroscience, 2023)
Introduction:In vitro models of traumatic brain injury (TBI) commonly use neurons isolated from the central nervous system. Limitations with primary cortical cultures, however, can pose challenges to replicating some aspects of neuronal injury associated with closed head TBI. The known mechanisms of axonal degeneration from mechanical injury in TBI are in many ways similar to degenerative disease, ischemia, and spinal cord injury. It is therefore possible that the mechanisms that result in axonal degeneration in isolated cortical axons after in vitro stretch injury are shared with injured axons from different neuronal types. Dorsal root ganglia neurons (DRGN) are another neuronal source that may overcome some current limitations including remaining healthy in culture for long periods of time, ability to be isolated from adult sources, and myelinated in vitro. Methods: The current study sought to characterize the differential responses between cortical and DRGN axons to mechanical stretch injury associated with TBI. Using an in vitro model of traumatic axonal stretch injury, cortical and DRGN neurons were injured at a moderate (40% strain) and severe stretch (60% strain) and acute alterations in axonal morphology and calcium homeostasis were measured. Results: DRGN and cortical axons immediately form undulations in response to severe injury, experience similar elongation and recovery within 20 min after the initial injury, and had a similar pattern of degeneration over the first 24 h after injury. Additionally, both types of axons experienced comparable degrees of calcium influx after both moderate and severe injury that was prevented through pre-treatment with tetrodotoxin in cortical neurons and lidocaine in DRGNs. Similar to cortical axons, stretch injury also causes calcium activated proteolysis of sodium channel in DRGN axons that is prevented by treatment with lidocaine or protease inhibitors. Discussion: These findings suggest that DRGN axons share the early response of cortical neurons to a rapid stretch injury and the associated secondary injury mechanisms. The utility of a DRGN in vitro TBI model may allow future studies to explore TBI injury progression in myelinated and adult neurons.